Síntese por redução carbotérmica assistida por micro-ondas de carbeto de zircônio - Gaviria, Juan Pablo Yasnó (2013)
One of the major motivations for the development of new synthesis routes is a continuing need for fast and energy-efficient methods that allow obtaining materials with differentiated technological characteristics and properties. The use of microwaves in materials synthesis has generated great interest in the scientific research due to its speed, simplicity and energy-efficiency. Among different synthesis methods which can be assisted by microwave energy, the carbothermal reduction is the most simple and effective method in ceramic materials production. The conventional carbothermal reduction is used to obtain zirconium carbide (ZrC). In this context, the purpose of this work was to study the synthesis by microwave-assisted carbothermal reduction of ZrC using a mixture of zirconia (ZrO2) and carbon black (C). The synthesis parameters evaluated in this work were: stoichiometry, ZrO2/C-forming process, microwave power, reaction time and pressure of inert gas (argon). Characterization by X-ray diffraction (XRD) analysis of the samples synthesized by this method showed that the formation of ZrC phase was enhanced by controlling the following parameters: microwave power and reaction time increases, conservation of theoretical stoichiometry ZrO2/C:1/3, less compression of the pelleted mixture before the reaction and moderate pressure of argon. The samples with the highest ZrC content were characterized by specific surface area (BET) and scanning electron microscopy (SEM). These characterizations revealed that microwave-assisted carbothermal reduction synthesis produced ZrC samples with average particle size of ~100-200nm, near the nanometer range, homogeneous morphology and reaction time of 30 minutes.